Методы симметризации в задаче Hele-Shaw - Васильева, Н.В. (Нелинейные граничные задачи, 2000)
The Hele-Shaw problem has studied in the paper. Estimates of both solutions’ support and time of their existence have been obtained with the methods of symmetrized.